Unravelling Yu Guangzhong’s identity through his poetic reflections: a corpus-based investigation - Li, Shengnan; Abdul Halim, Hazlina; Mamat, Roslina (Academy Publication, 2024)
This study examines Yu Guangzhong’s identity presented in his self-translated poetry collection, The Night Watchman. It employs corpus linguistic methodologies and utilizes the corpus linguistic tool AntConc for analysis. This study highlights Yu Guangzhong’s identity, which is presented in different categories and topics of poems. It is found that Yu Guangzhong’s identity is ever-changing, varying at different times, and occasionally conflicting and opposing. This study may have practical implications for Chinese literature and culture looking to enhance their international influence, and it may also provide academic insights for investigating other literary giants.